Assessment of resources for physical activity and understanding people's perception and practices regarding physical activity in an Indian city - Susheel Gautam; Kruthika B N; Akashanand; Aaheli Roy; Pradeep S. Banandur; Arvind Anniappan Banavaram (BMC, 2023)
Abstract Background Promoting physical activity in urban India is imperative considering the burden of non-communicable diseases in the country. Planning for improving population level physical activity needs sound understanding of availability and quality of resources/facilities for physical activity and knowing people's perception and practices regarding the physical activity. Methods A cross-sectional study was undertaken in Kolar city of Karnataka state in India. All the resources/facilities required for supporting physical activity were mapped and their quality was assessed utilizing adapted version of physical activity resource assessment questionnaire. The information regarding latitude, longitude and approximate size of the resource was obtained using a hand-held GPS tracker. 495 individuals aged ≥ 18 years, selected by two stage cluster random sampling with probability proportionate to population size technique, were interviewed to assess their perception and practices regarding physical activity using semi-structured questionnaire and global physical activity questionnaire. Results Kolar city has 36.3 physical activity resources per lakh population and per person availability of park and playground area was 0.4 Sq. meters. Available resources were concentrated in the center of the city. Half of the sports facilities and 14 of the 17 recreational facilities in the city were of poor to mediocre quality. 38.2% of adults in Kolar city were found to be physically active. Only 19.2% of the study participants had accessed sports/fitness facilities/playgrounds in past 3 months and only 18.8% of the study participants accessed parks in the previous 3 months. 28.6% to 59.1% of the participants preferred 'walking' for work, college and shopping. Less than 5% of the participants preferred and used cycle as a mode of transport. 1/3rd of the study participants felt that Kolar city is safe of walking and 44.6% felt that the city is safe for cycling. Conclusion Creating enabling environment by increasing the number and quality of resources/facilities for physical activity along with their equitable distribution is required to promote and improve population level physical activity in Kolar city. Urban planning with a focus on non-motorized transport including walking would contribute to improved people's perception and practices regarding physical activity in the city.